Manajemen Strategi Pemasaran Jasa Pendidikan Raudhatul Athfal Al-Muqoddasah Cimaung - Afni Fauziyah Saepulloh; Badrudin Badrudin (MANAZHIM, 2023)
Education is one of the most important aspects of human life. Education requires good management, because in it there are other individuals with different types of traits, characters and thoughts, who are both in the process of achieving the same ultimate goal, namely organizational goals. In fact, the goals of educational institution organizations are competing to become superior educational institutions. To achieve this goal, an initial strategy is needed in promoting the institution which is called marketing of educational services. Educational institutions compete in designing excellent programs that are very diverse in order to attract customers to send their children to these institutions. This study intends to reveal the strategy used by Raudhatul Athfal Cimaung in marketing educational services using descriptive qualitative research methods through the stages of data collection by observing, interviewing interested parties and analyzing institutional documents. The results of the study show that Raudhatul Athfal Al-Muqoddasah Cimaung has a superior program that instills good morals in early childhood. Where this age is the golden age of children where brain and physical growth and development grow and develop optimally. Furthermore, this study presents strategic management in the marketing of educational services according to the concept of the marketing mix, abbreviated as 7P, which includes Product, Price, Place, Promotion, People, Physical Evidence, and Process.